Nursing performance under high workload: a diary study on the moderating role of selection, optimization and compensation strategies. (6th November 2015) - Baethge, Anja; Müller, Andreas; Rigotti, Thomas
Abstract: Aims: The aim of this study was to investigate whether selective optimization with compensation constitutes an individualized action strategy for nurses wanting to maintain job performance under high workload. Background: High workload is a major threat to healthcare quality and performance. Selective optimization with compensation is considered to enhance the efficient use of intra‐individual resources and, therefore, is expected to act as a buffer against the negative effects of high workload. Design: The study applied a diary design. Over five consecutive workday shifts, self‐report data on workload was collected at three randomized occasions during each shift. Self‐reported job performance was assessed in the evening. Self‐reported selective optimization with compensation was assessed prior to the diary reporting. Methods: Data were collected in 2010. Overall, 136 nurses from 10 German hospitals participated. Selective optimization with compensation was assessed with a nine‐item scale that was specifically developed for nursing. The NASA‐TLX scale indicating the pace of task accomplishment was used to measure workload. Job performance was assessed with one item each concerning performance quality and forgetting of intentions. Results: There was a weaker negative association between workload and both indicators of job performance in nurses with a high level of selective optimization with compensation, compared with nurses with a low level. Considering the separate strategies, selection and compensation turned out to be effective. Conclusion: The use of selective optimization with compensation is conducive to nurses' job performance under high workload levels. This finding is in line with calls to empower nurses' individual decision‐making.